Skrining Assist Information System v3.1 at the National Narcotics Agency of Sidoarjo Regency - Nella Prima Yeni; Ade Eviyanti (CV. Media Digital Publikasi Indonesia, 2026)
The Screening Assist Information System v3.1 is a web-based application designed to support the substance abuse screening process at the National Narcotics Agency (BNN) of Sidoarjo Regency. This system uses the ASSIST (Alcohol, Smoking and Substance Involvement Screening Test) method from the WHO as an early detection tool for substance use risks. The system was developed using a Research and Development (R&D) approach with the Waterfall model in the System Development Life Cycle (SDLC). This information system was created using the PHP programming language and Mysql database. With its time efficiency, scoring accuracy, and data security, this system is an effective digital solution in supporting efforts to prevent and combat drug abuse in the Sidoarjo Regency. The system evaluation was conducted using the Blackbox Testing method, which showed that all features functioned properly, and the User Acceptance Testing (UAT) method was used to measure user satisfaction with a result of 87.6% . This percentage reflects the expectation that students provided honest answers, so that the data obtained was close to the actual level of validity. Overall, the evaluation results indicate that the developed information system can serve as an effective, adaptive digital solution that supports professional and structured efforts to prevent and address drug abuse.